A community-informed transdisciplinary approach to coastal restoration planning: Maximizing the social and ecological co-benefits of wetland creation in Port Fourchon, Louisiana, USA - Hemmerling, Scott A.; DeMyers, Christine; Parfait, Jessica; Piñero, Edwin; Baustian, Melissa M.; Bregman, Martijn; Di Leonardo, Diana; Esposito, Christopher; Georgiou, Ioannis Y.; Grismore, Audrey; Jung, Hoonshin; McMann, Brett; et al. (Frontiers in Environmental Science, 2023)
Port Fourchon is a vital staging area for Gulf of Mexico energy production and is strategically located in the Barataria-Terrebonne Estuary System, a biologically and economically productive ecosystem bounded by the Atchafalaya and Mississippi Rivers. This is also one of the most fragile and rapidly evolving landscapes in the United States, making the port and surrounding communities highly vulnerable to natural hazards and the impacts of climate change. Building resilience to climate-based disruptions is vital to Port Fourchon and other businesses operating in this dynamic landscape. The port plans to deepen its channel to 50 feet (15 m) to service larger vessels, generating millions of cubic yards of sediment and seeks to beneficially utilize this sediment to develop natural and nature-based solutions to help prepare for future challenges. To accomplish this goal, an Environmental Competency Group consisting of residents, coastal scientists, and key stakeholders was convened to co-develop and evaluate a series of marsh creation projects utilizing this sediment that will maximize social and ecological co-benefits and enhance the resilience of Port Fourchon and the surrounding communities. The group utilized participatory modeling and social return on investment methods to model long-term changes to the landscape and wetland vegetation communities resulting from the co-developed restoration strategies and assess the social value of these strategies. Residents who live and work around Port Fourchon were included in all stages of this research, including development and prioritization of potential restoration areas, identifying important physical and ecological parameters that should be modeled, evaluation of model results, and assessment of the social values expected to be generated by each restoration alternative under consideration. The transdisciplinary approach used in this research highlights the effectiveness of a community-informed, systematic approach to coastal restoration planning in building community resilience and ecosystem sustainability. This study provides approaches and tools that can be adapted for use elsewhere to develop holistic solutions that maximize the social, ecological, and economic co-benefits of coastal restoration.